2019
DOI: 10.1177/0267659119870725
|View full text |Cite
|
Sign up to set email alerts
|

MiR-421 inhibition protects H9c2 cells against hypoxia/reoxygenation-induced oxidative stress and apoptosis by targeting Sirt3

Abstract: Background: MicroRNAs (miRNAs) are involved in myocardial ischemia-reperfusion injury. miRNA-421 (miR-421) plays a significant role in the initiation of apoptosis and myocardial infarction. However, the molecular regulation of miR-421 in myocardial ischemia-reperfusion injury requires further elucidation. Methods: An in vitro hypoxia/reoxygenation model was established, and the expression levels of miR-421 and Sirtuin-3 (Sirt3) in H9c2 cells were quantified using quantitative real-time polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…Therefore, it is of great significance to explore the molecules that can affect the occurrence of TC. miRNA is a kind of non-coding RNA, non-coding protein, which is often used as upstream regulatory molecule to affect the biological process of many tumors and plays an important role in the occurrence and development of tumors (12)(13)(14). In TC, many studies have also reported that miRNA is involved in the regulation of its biological process.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great significance to explore the molecules that can affect the occurrence of TC. miRNA is a kind of non-coding RNA, non-coding protein, which is often used as upstream regulatory molecule to affect the biological process of many tumors and plays an important role in the occurrence and development of tumors (12)(13)(14). In TC, many studies have also reported that miRNA is involved in the regulation of its biological process.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, myocardial reperfusion can initiate oxidative stress through massive ROS generation, which further promotes myocardial injury inducing apoptosis and autophagy: this process is known as ischemia/reperfusion (I/R) injury. I/R injury has been adopted as a model to study MI and its mechanisms include a ROS burst during reperfusion, as well as calcium overload [61,62], resulting in increased apoptosis [63]. Conversely, SOD expression favors the post-ischemic cardiac function recovery, indicating the critical role of ROS and oxidative balance in MI and I/R.…”
Section: Myocardial Infarction and Ischemia/reperfusionmentioning
confidence: 99%
“…In the cardiac I/R settings, Liu et al demonstrated that silencing of miR-421 in vitro decreased apoptosis, and both MDA and LDH levels, and increased SOD levels, ultimately reverting I/R effects. Sirt3, the miR-421 target, was found downregulated after I/R and its expression inversely correlated to increased expression of miR-421 [62]. In lung cancer, the regulation of ROS by miR-421 has been associated with resistance to the chemotherapy drug paclitaxel [183].…”
Section: Mir-155 and Oxidative Stress In Cardiac And Pulmonary Diseasesmentioning
confidence: 99%
“…To determine which sEV-linked mediators may cause cardiomyocytes apoptosis post-PM 2.5 exposure, we explored literature and public sequencing data systematically based on biological function, circulating and EVs-packed abundance of exogenous microRNAs. We identified a well conserved, PM 2.5 -associated EVs-miRNA (miR-421, 1.26 ± 0.32, p = 0.0003 of PM 2.5 compared to control), based on previous reports (Rodosthenous et al, 2016;Shu et al, 2015) that played important roles in regulating smoke-associated lung injury (Izzotti et al, 2011) and hypoxia-associated cardiac infarction (Liu et al, 2020;Wang et al, 2015). As shown in Figure S3, subacute respiratory exposure to PM 2.5 increased the content of miR-421 (mmu-miR421-3p) in heart tissue and serum-derived sEV (Figure S3A-S3B).…”
Section:  Respiratory System Derived Sev Packaging Mir- Mediates...mentioning
confidence: 99%